Increased mitochondrial DNA4977-bp deletion in catheterization laboratory workers with long-term low-dose exposure to ionizing radiation. (June 2019) - Borghini, Andrea; Vecoli, Cecilia; Piccaluga, Emanuela; Guagliumi, Giulio; Picano, Eugenio; Andreassi, Maria Grazia
Aims: Ionizing radiation may lead to mitochondrial DNA (mtDNA) mutations and changes in mtDNA content in cells, major driving mechanisms for carcinogenesis, vascular aging and neurodegeneration. The aim of this study was to investigate the possible induction of common mitochondrial deletion (mtDNA4977) and mtDNA copy number (mtDNA-CN) changes in peripheral blood of personnel working in high-volume cardiac catheterization laboratories (Cath Labs). Methods: A group of 147 Cath Lab workers (median individual effective dose = 16.8 mSv, for the 41 with lifetime dosimetric record) and 74 unexposed individuals were evaluated. The occupational radiological risk score was computed for each subject on the basis of the length of employment, individual caseload and proximity to the radiation source. mtDNA4977 deletion and mtDNA-CN were assessed by using quantitative real-time polymerase chain reaction. Results: Increased levels of mtDNA4977 deletion were observed in high-exposure Cath Lab workers compared with unexposed individuals ( p  < 0.0001). Conversely, mtDNA-CN was significantly greater in the low-exposure workers ( p  = 0.003). Occupational radiological risk score was positively correlated with mtDNA4977 deletion (Spearman's r  = 0.172, p  = 0.03) and inversely correlated with mtDNA-CN (Spearman's r  = –0.202, p  = 0.01). In multiple regression model, occupational radiological risk score emerged as significant predictor of high levels of mtDNA4977 deletion (ß coefficient = 0.236, p  = 0.04). Conclusion: mtDNA4977 deletion is significantly high in Cath Lab personnel. Beyond the well-recognized nuclear DNA, mtDNA damage might deserve attention as a pathogenetic molecular pathway and a potential therapeutic target of ionizing radiation damage.